2022
DOI: 10.1002/pip.3634
|View full text |Cite
|
Sign up to set email alerts
|

Wafer‐scale Ge epitaxial foils grown at high growth rates and released from porous substrates for triple‐junction solar cells

Abstract: Germanium is listed as a critical raw material, and for environmental and economic sustainability reasons, strategies for lower consumption must be implemented. A promising approach is Ge lift‐off concepts, which enable to re‐use the substrate multiple times. Our concept is based on the Ge‐on‐Nothing approach that is the controlled restructuring at high temperature of a macroporous Ge surface, forming a Ge foil weakly attached to its parent wafer. Its suitability as III–V epitaxy seed and support substrate has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Many applications can take advantage of this kind of versatility such as energy storage systems, [ 7 ] thermoelectric devices, [ 11 ] or nanoengineered compliant substrates for epitaxial growth. [ 21,23 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many applications can take advantage of this kind of versatility such as energy storage systems, [ 7 ] thermoelectric devices, [ 11 ] or nanoengineered compliant substrates for epitaxial growth. [ 21,23 ]…”
Section: Resultsmentioning
confidence: 99%
“…Many applications can take advantage of this kind of versatility such as energy storage systems, [7] thermoelectric devices, [11] or nanoengineered compliant substrates for epitaxial growth. [21,23] The demonstration of wafer-scale production and use of porous Ge substrates for various applications, comes with a crucial need to develop fast and nondestructive characterization methods easily applicable for post-production PGe wafer's quality assessment. To date, PGe layers are mainly characterized by SEM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, this generates various defects in the layer, it has been shown that high efficiency devices can be still fabricated on such a substrate, with limited inuence on their performance. 21 Recently, another technique called Germanium-on-Nothing 7,22 (GoN) has been demonstrated. This process uses a sequence of photolithography, plasma etching, and annealing steps to engineer a voided weak layer at the interface between the bulk material and the Ge NM, which enables the separation of the membrane from the substrate.…”
Section: Introductionmentioning
confidence: 99%